2010
DOI: 10.1115/1.3205024
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Characteristics of HCCI in Motorcycle Engine

Abstract: Homogeneous charge compression ignition (HCCI) is recognized as an advanced combustion system for internal combustion engines that reduces fuel consumption and exhaust emissions. This work studied a 150 cc air-cooled, four-stroke motorcycle engine employing HCCI combustion. The compression ratio was increased from 10.5 to 12.4 by modifying the cylinder head. Kerosene fuel was used without intake air heating and operated at various excess air ratios (λ), engine speeds, and exhaust gas recirculation (EGR) rates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Temperature is the most critical factor in HCCI combustion [34]. In this study, cylinder head and oil temperatures were maintained above 120 • C and 65 • C, respectively, for stable HCCI operation [35]. The engine was started with the original SI system and warmed up to achieve these temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…Temperature is the most critical factor in HCCI combustion [34]. In this study, cylinder head and oil temperatures were maintained above 120 • C and 65 • C, respectively, for stable HCCI operation [35]. The engine was started with the original SI system and warmed up to achieve these temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…After these thermistors are connected with the input interface, Motohawk ECU for thermistor, voltage signals can be generated and read for engine control algorithm. In this study, cylinder head and oil temperature are kept above 120°C and 65°C respectively for stable HCCI operation (Wu et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study has shown that HC and CO emissions, and coefficient of cycle variation (COV) of indicated mean effective pressure (IMEP) could be decreased during closed valve injection (Wu et al, 2010). Therefore, the fuel injection timing of 90 o bTDC (before top dead center) of compression stroke was chosen for experiments not only to avoid the liquid fuel from entering the cylinder directly but also to maintain the homogeneity of the air-fuel mixture.…”
Section: Methodsmentioning
confidence: 99%
“…After these thermistors were connected to the input interface, Motohawk ECU for thermistor, voltage signals could be generated and read for engine-control algorithms. In this study, cylinder head and oil temperatures were held above 120°C and 65°C, respectively, for stable HCCI operation (Wu et al, 2010). …”
Section: Methodsmentioning
confidence: 99%
“…A fuel injection timing of 90° bTDC (before top dead center) of the compression stroke was chosen not only to prevent the liquid fuel from entering the cylinder directly but also to maintain the homogeneity of the air-fuel mixture (Wu et al, 2010).…”
Section: Testingmentioning
confidence: 99%